Implementation of Modern Pedagogical Technologies in the Context of Increasing the Efficiency of the Educational Process - Pliushch, Valentina; Sorokun, Svitlana (Journal of Ecohumanism, 2024)
The implementation of modern pedagogical technologies is transforming the landscape of education, enhancing the efficiency and effectiveness of learning processes. These technologies, ranging from interactive whiteboards and learning management systems to advanced AI-driven tools, play a crucial role in creating engaging and personalized learning experiences. The purpose of the article is the implementation of modern pedagogical technologies in the context of increasing the efficiency of the educational process. The object of the study is modern pedagogical technologies. The research methodology involves the use of the IDEF0 methodology. As a result of the study, the IDEF0 model of implementation of modern pedagogical technologies in the context of increasing the efficiency of the educational process is presented.